The spatial economy: Cities, regions, and international trade - Fujita, M; Krugman, P; Venables, A (MIT Press, 1999)
Explores how a common approach that emphasizes the three-way interaction among increasing returns, transportation costs, and the movement of productive factors can be applied to a wide variety of issues in regional, urban, and international economics. Introduces the basic approach in the context of "regional" models in which "agriculture" is the primary sector and is immobile across locations but "manufacturing" is a sector that is subject to increasing returns and can move between regions and discusses the Dixit-Stiglitz model of monopolistic competition and its spatial implications; how interactions among increasing returns at the level of the firm, transport, costs, and factor mobility can cause spatial economic structure to emerge and change; the case of multiregional economics; and the consequences of costly agricultural transport. Considers the location of cities in a world in which everything is mobile, examining a heuristic approach to the spatial modeling of urban systems; the monocentric economy; the emergence of new cities; the evolution of a hierarchical urban system; the size of cities; and how variations in the natural landscape, such as ports and rivers, can influence urban location. Explores international trade, discussing international specialization; economic development and the spread of industry; industrial clustering; the emergence of regions of specialization in a borderless world with continuous space; and the possible interaction between international trade and the process of urbanization within nations. Fujita is at the Kyoto Institute of Economic Research, Kyoto University. Krugman is at the Massachusetts Institute of Technology. Venables is at the London School of Economics. Index.